Effectiveness of Different Behavior Management Techniques in Pediatric Dentistry - Rajnish Kumar Verma; Rutuja Sindgi; Deepthi Nirmal Gavarraju; Pappu Lakshmi Manasa; Prashanth Kumar Bakkuri; Alok Dubey; Sandeep Reddy Ravula (Journal of Pharmacy and Bioallied Sciences)
Background: Pediatric dentistry necessitates efficient behavior management methods to ensure successful treatment outcomes and positive experiences for young patients. This research aims to evaluate the comparative effectiveness of “Tell-Show-Do (TSD)”, positive reinforcement, nitrous oxide sedation, and pharmacological sedation in pediatric dental practice. Methods: A retrospective analysis was conducted on pediatric patients aged 3-12 years who underwent dental treatment at a designated dental center over a 1-year period. Patients were categorized based on the behavior management method utilized: TSD, positive reinforcement, nitrous oxide sedation, or pharmacological sedation. Treatment success rates and patient cooperation levels were evaluated for each method. Results: Positive reinforcement and TSD demonstrated the highest treatment success rates (85% and 80%, respectively) and patient cooperation levels (90% and 85%, respectively). Nitrous oxide sedation exhibited moderate effectiveness with a treatment success rate of 70% and a patient cooperation level of 75%. Pharmacological sedation had the lowest treatment success rate (60%) and patient cooperation level (65%). Statistical analysis revealed significant differences in treatment success rates (P < 0.05) and patient cooperation levels (P < 0.05) among the behavior management methods. Conclusion: Positive reinforcement and TSD emerge as highly efficient behavior management methods in pediatric dentistry, promoting high treatment success rates and patient cooperation levels. Nitrous oxide sedation offers a valuable adjunct for managing anxiety and enhancing patient comfort. Pharmacological sedation, while efficient in certain cases, should be used judiciously due to associated risks.